2008
DOI: 10.1128/jcm.01102-08
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Outcome of Hepatitis A Virus (HAV) Infection in a Traveler with Incomplete HAV Vaccination and Evidence of Rift Valley Fever Virus Infection

Abstract: Hepatitis A virus (HAV) infection is rarely fatal except in patients with chronic liver disease. In the case reported here, an elderly women died of HAV infection 12 years after incomplete HAV vaccination. The possible role of a concordant Rift Valley fever virus infection acquired in Kenya is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 9 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…As also humans may serve as amplifying hosts, the introduction of RVFV by viremic humans seems possible and probable. In 2008, one case of RVF was diagnosed retrospectively in Germany in an ill woman, who had returned from Africa [ 86 ]. However, few data exist on the vector competence of European mosquito species for RVFV.…”
Section: Introductionmentioning
confidence: 99%
“…As also humans may serve as amplifying hosts, the introduction of RVFV by viremic humans seems possible and probable. In 2008, one case of RVF was diagnosed retrospectively in Germany in an ill woman, who had returned from Africa [ 86 ]. However, few data exist on the vector competence of European mosquito species for RVFV.…”
Section: Introductionmentioning
confidence: 99%
“…Severity of human RVF was associated with the presence of concomitant co-infections. A fatal outcome in a travel related case was attributed to the presence of concurrent hepatitis A virus infection [ 45 ]. Additionally, a study in South Africa during the 2010 RVFV outbreak indicated that existing HIV-positive infection status was associated with risk of the encephalitic form of RVF disease [ 129 ], a finding similar to experience among HIV-infected patients in Tanzania in 2007, where all patients with HIV-positive status developed encephalitis, and of whom 75% died [ 123 ].…”
Section: Resultsmentioning
confidence: 99%
“…Instead they are strongly linked to excess rainfall and to local flooding events [24] and the consequent rise in mosquito abundance [25][26][27][28][29][30][31][32]. In addition, there is mounting evidence that suggests that there is continuing low-level RVFV transmission to humans and to animals between recognized epidemic periods [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49]. Undetected infections, particularly in livestock, provide an important reservoir for recurrent outbreaks, leading to a continuing threat of disease in economically marginal communities and risk of further geographical expansion.…”
Section: Introductionmentioning
confidence: 99%